Comparison of Clinical and Genetic Characteristics of Familial Mediterranean Fever Patients Among Adult Age Groups - Fidan, Sami; Seferli, Sahile; Durak, Serdar; Seferoğlu, Ceren Konca; Okatan, İlyas Ercan; Han Çebi, Alper; Erkut, Murat; Mansur Coşar, Arif (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Familial mediterranean fever (FMF) is a genetic autoinflammatory disease typically diagnosed in childhood. In this study, we aimed to investigate the demographic, clinical, and genetic characteristics of patients aged 18 years and older who were diagnosed with FMF. Materials and Methods: Patients diagnosed with FMF between 2014 and 2022 at Karadeniz Technical University Faculty of Medicine Hospital were included in the study. Patients were divided into 2 groups based on the age of disease onset. Group I included patients with adult-onset (ages 18-40), while group II comprised patients with late onset (ages 40 and above). Subsequently, the 2 groups were compared. Results: A total of 150 patients with a mean age of 32 (18-79) were included in the study. There were 116 patients in group I and 34 (22.7%) in group II. The most common presenting complaint was abdominal pain (91.3%), and the most prevalent complication was amyloidosis (4.7%). No significant differences were observed between age groups regarding clinical findings and symptoms. The most frequent homozygous mutations were M694V (9.3%) and R202Q (1.8%), while the heterozygous mutations were M694V (37.3%) and R202Q (35.5%), respectively. The rate of M694V gene positivity in the adult-onset group was significantly higher compared to the lateonset group (52.9% and 25%, respectively, P = .020). Conclusion: There does not appear to be a significant difference in clinical signs and symptoms between adult-onset and late-onset FMF patients. The higher rate of M694V gene positivity in the adult-onset group suggests that the M694V mutation may be responsible for the early expression of the disease. Cite this article as: Fidan S, Seferli S, Durak S, et al. Comparison of clinical and genetic characteristics of familial Mediterranean fever patients among adult age groups. Turk J Gastroenterol. 2024;35(8):618-624.